2023
DOI: 10.3390/foods12244491
|View full text |Cite
|
Sign up to set email alerts
|

Active and Intelligent Biodegradable Packaging Based on Anthocyanins for Preserving and Monitoring Protein-Rich Foods

Bifen Zhu,
Yu Zhong,
Danfeng Wang
et al.

Abstract: Currently, active and intelligent packaging has been developed to solve the spoilage problem for protein-rich foods during storage, especially by adding anthocyanin extracts. In such a film system, the antioxidant and antibacterial properties were dramatically increased by adding anthocyanins. The physicochemical properties were enhanced through interactions between the active groups in the anthocyanins and reactive groups in the polymer chains. Additionally, the active and intelligent film could monitor the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Having this in mind, several studies have been reported in the literature to assess the degree of conservation of perishable foods such as meat, fish, and dairy products using pH-sensitive natural dyes, namely anthocyanins, to develop colorimetric pH-responsive films that act as indicators of food freshness in real-time. However, the use of such dyes for these applications is still limited because they lose more than 50% of their color between pH 4 and 7, a critical range for monitoring color changes during food spoilage, due to the establishment of a complex chemical equilibrium network involving reversible reactions such as hydration, tautomerization, isomerization, as well as irreversible oxidative degradation mechanisms. …”
Section: Introductionmentioning
confidence: 99%
“…Having this in mind, several studies have been reported in the literature to assess the degree of conservation of perishable foods such as meat, fish, and dairy products using pH-sensitive natural dyes, namely anthocyanins, to develop colorimetric pH-responsive films that act as indicators of food freshness in real-time. However, the use of such dyes for these applications is still limited because they lose more than 50% of their color between pH 4 and 7, a critical range for monitoring color changes during food spoilage, due to the establishment of a complex chemical equilibrium network involving reversible reactions such as hydration, tautomerization, isomerization, as well as irreversible oxidative degradation mechanisms. …”
Section: Introductionmentioning
confidence: 99%
“…Compared with synthetic pigments, natural pigments have higher stability and safety. Among them, anthocyanins are one of the best natural substitutes for artificially synthesized pigments and have been used widely because of their good biological activities and safety [ 3 ]. Numerous studies have confirmed that anthocyanins exhibit various biological activities including antioxidant, anti-tumor, anti-inflammatory, hypoglycemic, vision protection, and anti-aging [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the research on the stabilization of anthocyanins is currently a hot topic that urgently needs to be addressed. Previous studies have found that copigmentation, structural modification, and encapsulation strategies could significantly improve the stability of anthocyanins [ 1 , 3 ]. However, these methods still have problems such as low yield, poor safety, and difficulty in maintaining the color of anthocyanins.…”
Section: Introductionmentioning
confidence: 99%